CUSTOMER SATISFACTION WITH ALOE VERA GEL PRODUCTS TO INCREASE THE ECONOMIC VALUE OF BAAN TALAY HOME COMMUNITY ENTERPRISES, HAT CHAO SAMRAN SUBDISTRICT, MUEANG PHETCHABURI DISTRICT, PHETCHABURI - Ampilasai, Suthasinee (Journal of Multidisciplinary Academic Research and Development (JMARD), 2022)
This article developed aloe vera gel products and examined consumer satisfaction with aloe vera gel products to increase economic value of Baan Talay Home community enterprises in Hat Chao Samran subdistrict, Mueang Phetchaburi District, Phetchaburi. From an unknown population size, samples were calculated by the Cochran formula at 95%. 384 samples were chosen by accidental sampling, with data collected from 400 samples to ensure accuracy. Results were that improved product design, packaging, and product quality potentially increase market opportunities. Folk wisdom and appropriate technology were applied conceptually to develop other products. The packaging component consisted of properties, instructions, ingredients, warnings, quality standards, net weight, expiration date, distribution site, and production. In terms of customer satisfaction with aloe vera gel, demography affected customer satisfaction with soft and smooth gel texture, skin moisturizing, dullness and wrinkle elimination, absorption into skin, attractive packaging, appropriate volume, and clear label ingredient details at a significance level of 0.05, respectively.